The power of comics history, form and culture - Duncan, Randy 1958-; Smith, Matthew J. 1971-; Levitz, Paul 1956- (Bloomsbury, 2015)
Offers undergraduate students with an understanding of the comics medium and its communication potential. This book deals with comic books and graphic novels. It focuses on comic books because in their longer form they have the potential for complexity of expression.